دور صندوق الزكاة في تمويل المشاريع الاستثمارية دراسة تطبيقية لصندوق الزكاة لولاية سيدي بلعباس للفترة الممتدة من 2003 إلى 2018 - زهرة دريش . محمد الخطيب نمر . (جامعة الوادي - University of Eloued, 2020)
لقد تم التطرق في هذه الدراسة إلى موضوع "دور صندوق الزكاة في تمويل المشاريع الاستشارية في الجزائر"، و تم إسقاط الدراسة التطبيقية على صندوق الزكاة لولاية سيدي بلعباس،بالاعتماد على تفسير وتحليل الإحصائيات و مؤشرات تتعلق بنمو حصيلة الزكاة و أشكال استغلالها والمشاريع المعمولة عبر آلية القرض الحسن . ومن أهم النتائج المتوصل إليها التطور و المستمر لحصيلة زكاة المال المحصل عليها بولاية سيدي بلعباس،تزايد عدد العائلات المستفيدة من صندوق الزكاة وكذا تطور حجم المبالغ المخصصة للاستثمار، الا أنه مازال يعاني من بعض الإختلالات منها نسبة تمويل النشاطات الصناعية والفلاحية . Summary The theme of this study, titled "The Role of the Zakat Fund in the Financing of Investment Projects in Algeria", was carried out in the locality of Sidi Bel Abbés based on the analysis of statistics as well as that the Indices concerning the development of the harvest as well as the forms of background of use see the projects engaged through the mechanism of al kard al hacen Among the results obtained is the continuous increase in the revenues of zakat el mal harvested through the state of Sidi Bel Abbés, the increase in the number of families benefiting from the zakat fund and the increase of the amounts designated for investment. Nevertheless the bottom of the zakat knows some insufficiencies cited the lack of financing of the industrial and agricultural activities
The Role of Zakat Fund in Financing Investment Projects Case Study of the Zakat Fund for the State of Sidi Bel Abbes-AlgeriaThe period from 2003 to 2018
Keywords: صندوق الزكاة ; المشاريع الاستثمارية ; القرض الحسن ; زكاة المال